Pengembangan Media Kotak Pintar Menggunakan Bahan Bekas - Elma Sabrina Putri; Muhammad Guntur; Pertiwi Kamariah Hasis (YAYASAN YASZOY CAYAHA NUSANTARA, 2024)
This study aims to determine the needs analysis, validity, and practicality of the media, and to determine the effectiveness of the learning media developed. This type of research is the mixed method with the ADDIE development model which consists of five stages, namely: Analysis, Design, Development, Implementation and Evaluation. The subjects of this study were 8 students of Group B1 at TK Negeri Pembina Telluwanua Palopo City. The instruments used was a questionnaire of media expert validation, materials, and educator practicality. The data analysis technique used was descriptive quantitative and quantitative analysis.The result of the researcher’s development in the form of Smart Box learning media made from used materials. The results of the needs analysis experienced by students include : a lack of attention of students during learning, and the media used is only a blackboard in the early literacy process in recognizing letters. The results of media expert validation obtained an average of 84,44% with the category “Very Valid”, the results of the material expert validation recapitulation obtained an average of 84% with the category “Very Valid”, and the results of the practicality test by educatiors obtained an average of 100% with the category “Very Practical”. The result of the Smart Box effectiveness test are seen from the development of children’s abilities through daily assesments on the Independent Curriculum.Based on these result, it can be conceled that the Smart Box media using used materials is effective in the learning proses.